The cytotoxicity effect of Metalloprotease produced and isolated from Aeromonas spp. - Abdallah, Muhannad M.; H. Saleh, Tahreer (The Iraqi Journal of Veterinary Medicine, 2018)
One hundred and fifty stool sampling were collected from clinical sources responsible of causing diarrhea in adults as well as children. The identification of Aeromonas hydrophila isolates depended on common methods of identification dependent on biochemical characteristics and culture, then vitek2 compact system was used. Eight Aeromonas hydrophila isolates were gained and revealed various productivity of metalloprotease; the isolate number 8 was the maximum effective in metalloprotease production. The eight isolates were examined with Polymerase Chain Reaction to prove enzyme gene presence, the results revealed that all isolates were positive for ahMP genes; metalloprotease was completely purified via a number of steps, which included ammonium sulphate precipitation, dialysis, ion exchange and gel chromatography. Cytotoxicity effect of metalloprotease studies on cancer and normal cell lines, The results showed the purified metalloprotease as effective cytotoxic effect on liver hepatocellular cancer cells (HepG2) compared with no effect on normal liver cell line (WRL-68) indicating less cytotoxic effect.